Baruk : sebuah institusi sosial dan budaya masyarakat Bidayuh - Chali @ Charlie, Ungang (Universiti Malaysia Sarawak (UNIMAS), 2006)
This research seeks to understand the Bidayuh conception of the Baruk as an institution which remains as the most visible symbol of Bidayuh identity and unity. Observance of the role of the Baruk as center of ritual and social interaction has helped the Bidayuh to remain as a distinct cultural entity. The Baruk is not merely a head house as thought by orientalists. It helps to sanctify the Bidayuh adat, the most important element in their survival. It is an institution which is worth preserving. Nowadays, the Baruk has been reduced to a communal place of social interaction and a cultural relic of yesteryears in a modern tradition. In this research, the close relationship between its unique material artifacts, architectural design, and its ritual functions are portrayed